A study on service quality and student satisfaction at Perpustakaan Sultanah Bahiyah, Universiti Utara Malaysia (UUM) / Nor Syakiroh Ismail and Siti Shakinah Abu Masor - Ismail, Nor Syakiroh; Abu Masor, Siti Shakinah (2018)
Student satisfaction is an important aspect for the successfulness of academic library services. The purpose of this study is to examine the relationship between service quality and students' satisfaction. In addition, service quality dimension is one of the dimensions that contribute to students' satisfaction at academic library. Service quality includes reliability, assurance, tangibility, empathy and responsiveness. A survey was conducted at Perpustakaan Sultanah Bahiyah, Universiti Utara Malaysia (UUM). The data were collected using a self-administered questionnaire from 377 respondents using a stratified sampling technique. However only 279 responses with 74% response rate were deemed suitable for further analysis. The result of this study indicates that there is high level of students' satisfaction at PSB (UUM) and reliability is the most influential factor that contribute to students' satisfaction at PSB (UUM). This study reveals that all hypothesis on service quality dimensions listed were accepted.